1993
DOI: 10.1159/000139858
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ‘Contact Laxatives’ on Intestinal and Colonic Epithelial Cell Proliferation

Abstract: Experimental studies indicate that laxatives may induce epithelial damage. In addition, some laxatives induce the release of prostaglandins. Epithelial cell damage and release of prostaglandins are two pathways by which epithelial cell proliferation could be influenced. Furthermore, fermentable laxatives like lactulose may influence large intestine cell proliferation by the trophic effect of the fermentation products such as short-chain fatty acids. For these reasons an in vivo study in rats was performed to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…This study is a continuation of the one reported by Geboes et al [4], where cell prolif eration was measured.…”
Section: Introductionsupporting
confidence: 60%
See 2 more Smart Citations
“…This study is a continuation of the one reported by Geboes et al [4], where cell prolif eration was measured.…”
Section: Introductionsupporting
confidence: 60%
“…These findings appear to be particularly important because of minimal changes found in measurements of cell proliferation under the same conditions [4], In one of the mea surements (AE1 cytokeratin) the changes ap pear to be structural, and measurements of mucin could be derived from secretory changes with or without structural alterations. This enlarged series of biomarkers would ap pear to make available more comprehensive evaluations of cellular structure and function involving colonic epithelial cell proliferation and differentiation.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The guinea pig was chosen, as the myenteric plexus of this species is well characterized, and a reliable model of inflammation has been established. The incorporation of the thymidine analogue bromodeoxyuridine (5-bromo-2-deoxyuridine; BrdU) into replicating DNA was used to label proliferative cells (Gratzner 1982;Potten et al 1992;Geboes et al 1993), and single-and double-labelling immunohistochemistry was used to assess the occurrence of BrdU in specific cells of the myenteric plexus.…”
Section: Introductionmentioning
confidence: 99%
“…Increased cell proliferation in the rat intestine has also been reported for sennoside A and other active laxative compounds like danthron, bisacodyl and magnesium sulfate (Toyoda et al 1994). However, increased cell proliferation of the large intestine was not observed in other studies on rats following long-term exposure to a senna extract or pure sennosides (Mengs 1988;Geboes et al 1993;Lyden-Sokolowski et al 1993).…”
Section: Discussionmentioning
confidence: 84%